Response of jack bean (Canavalia ensiformis (L) DC) to potassium sources and application time - Marta Yuliani Velisitas Eklemis; Heni Purnamawati; Siti Marwiyah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Jack bean or koro pedang is a potential source as a soybean substitute for food and feed. In production, the plant is also useful in crop rotation and intercropping to support sustainable agriculture systems. However, jack bean production in Indonesia is still challenging. One of the obstacles in the production is the flowers and pods dropping, which reduces yield markedly. This study aimed to evaluate the source and timing of additional potassium fertilizer on the generative phase and yield of jack bean. The experimental design used a randomized complete block design with two factors, i.e., the source of potassium fertilizer as the first factor consisting of five levels: no fertilizer application, base fertilizer, base fertilizer + goat manure, base fertilizer + rice husk ash, and base fertilizer + KCl. The second factor was fertilization time, i.e., at 46 and 121 days after planting. The treatment of the potassium fertilizer source and fertilization timing affected several generative characters, but did not have much effect on productivity. Future studies should identify other potassium fertilizer sources to find the optimal dose to support plants in the generative phase. Keywords: additional potassium; flower drop; koro pedang; pod formation